A jegyzett társaságok (felügyelő) testületére vonatkozó EU-alapelvek Magyarországon - Keczer, Gabriella (Közép-Európai Közlemények, 2010)
In 2005 European Commission has launched a Recommendations concerning the (supervisory) boards of listed companies and invited the Member States to follow the published principles. Hungary has launched a Code for listed companies in 2008 on the basis of the EU-principles. In my paper I compare the EU Recommendations with the suggestions of the Hungarian Code, with document analysis. I also present the corporate governance system of one of the leading listed company in Hungary: MOL.